Analisis Korelasi Sikap Ilmiah dan Hasil Belajar Biologi : (Analysis Correlation of Scientific Attitude and Biological Learning Outcomes) - Muhammad Nasrul Mustain; Bonita Hirza; Rusdy A Siroj (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
This study intends to provide information: (1) the level of scientific attitude ability of Biology students (2) the level of learning outcomes of Biology lessons (3) see the relationship between scientific attitudes and learning outcomes in Biology. The type of research was correlation research. The research population was all high school students in Ogan Komering ilir district, which is taken 30% of the sample area so that 5 districts represent the population. The sample technique used is perposive sampling with a total of 1827 students and the instruments used are scientific attitude questionnaires and odd semester test scores for the 2020/2021 school year. The results showed ((1) students' scientific attitude obtained an average score of 89 in the medium category, (2) cognitive learning outcomes of Biology students obtained an average score of 82 in the medium category, (3) There was a significant relationship between scientific attitudes and cognitive learning outcomes in Biology lessons with a relationship level of 0.655 including a